PEST CONTROL OF APHIDS (Aphis gossypii) ON PEPPER PLANTS (Capsicum annum L.) USING AN EXTRACT OF CITRONELLA (Cymbopogan nardus L.) - Ahmat S. Mumba; Caroulus S. Rante (Jurnal Agroekoteknologi Terapan, 2020)
The cultivation of Pepper plants (Capsicum annuum L.) is the agricultural business that promises a profit is attractive because of the high market demand. Chili including  commodity agriculture that gets serious attention from the government and businesses because of its contribution to the national economy. The factors or constraints in the cultivation of pepper plants is plant pest (OPT), which is still one of the main constraints on the cultivation of Chili peppers. The pests that are found on land under cultivation Chili namely aphids. Keywords: chili., plant pest., commodity. AbstrakBudidaya tanaman Cabai (Capsicum annuum L.) merupakan kegiatan usaha tani yang menjanjikan keuntungan menarik karena permintaan pasar yang tinggi. Cabai termasuk komoditas pertanian yang mendapat perhatian serius dari pemerintah dan pelaku usaha karena kontribusinya terhadap perekonomian nasional. Kendala dalam budidaya tanaman Cabai adalah organisme pengganggu tumbuhan (OPT) yang masih menjadi salah satu kendala utama pada budidaya cabai. Hama yang ditemukan pada lahan budidaya Cabai, yaitu kutu daun aphid. Kata kunci:  cabai., OPT., komoditi.